The Role of Science from the Perspective of the Qur'an and Hadith - Nur Fadhilah; Moch. Miftahur Rohman; Dwi Kartika Putri; Meisya Sakhiya Amanda; Hamidatun Nihayah (Aslim: Journal of Education and Islamic Studies, 2026)
Knowledge is an essential aspect of human life that plays a significant role in the development of civilization and the attainment of well-being. In the perspective of the Qur'an and Hadith, knowledge is not only seen as a means for worldly progress but also as a path to achieving happiness in the afterlife. This article seeks to analyze the role of knowledge from the perspective of the Qur'an and Hadith and to address the question of how influential it is in both worldly and eternal life. This study employs a qualitative approach by examining Qur'anic verses and Hadiths related to knowledge. The findings indicate that the Qur'an and Hadith emphasize the importance of knowledge as a key to achieving goodness in both this world and the hereafter. In Islam, knowledge serves a dual function: as a provision for facing worldly challenges and as a means to earn rewards and draw closer to Allah in the hereafter. Therefore, knowledge, from the perspective of the Qur'an and Hadith, has a profound influence in guiding Muslims to lead a life of wisdom and serves as a form of worship that brings positive benefits both in this world and in the hereafter.